Two weeks of moderate-intensity continuous training, but not high-intensity interval training, increases insulin-stimulated intestinal glucose uptake - Motiani KK; Savolainen AM; Eskelinen JJ; Toivanen J; Ishizu T; Yli-Karjanmaa M; Virtanen KA; Parkkola R; Kapanen J; Gronroos TJ; Haaparanta-Solin M; Solin O; et al. (My University, 2022)
Similar to muscles, the intestine is also insulin resistant in obese subjects and subjects with impaired glucose tolerance. Exercise training improves muscle insulin sensitivity, but its effects on intestinal metabolism are not known. We studied the effects of high intensity interval training (HIIT) and moderate intensity continuous training (MICT) on intestinal glucose and free fatty acid uptake from circulation in humans. Twenty-eight healthy middle-aged sedentary men were randomized for two weeks of HIIT or MICT. Intestinal insulin-stimulated glucose uptake and fasting free fatty acid uptake from circulation were measured using positron emission tomography and [18F]FDG and [18F]FTHA. In addition, effects of HIIT and MICT on intestinal Glut2 and CD36 protein expression were studied in rats. Training improved aerobic capacity (p=0.001) and whole-body insulin sensitivity (p=0.04), but not differently between HIIT and MICT. Insulin-stimulated glucose uptake increased only after the MICT in the colon [HIIT=0%; MICT=37%] (p=0.02 for time*training) and tended to increase in the jejunum [HIIT=-4%; MICT=13%] (p=0.08 for time*training). Fasting free fatty acid uptake decreased in the duodenum in both groups [HIIT=-6%; MICT=-48%] (p=0.001 time) and tended to decrease in the colon in the MICT group [HIIT=0%; MICT=-38%] (p=0.08 for time*training). In rats, both training groups had higher Glut2 and CD36 expression compared to control animals. This study shows that already two weeks of MICT enhances insulin-stimulated glucose uptake while both training modes reduce fasting free fatty acid uptake in the intestine in healthy middle-aged men, providing an additional mechanism by which exercise training can improve whole body metabolism.